CITRA LESBIAN DALAM NOVEL INDONESIA AWAL TAHUN 2000-AN KARYA PEREMPUAN PENGARANG - Kasnadi Kasnadi (LITERA, 2017)
AbstractThis study aims to describe lesbians’ identity, interaction, struggle, and other figures’ views of the existence of lesbian characters in Indonesian novels by female writers inthe early 2000’s. This was a qualitative descriptive study. The data were collected by thedocumentation technique using the reading-recording strategy. The data analysis usedthe content analysis technique. The results of the study are as follows. First, the identityof lesbian characters includes: (a) lesbians of “butch”, “femme”, and “andro” types; (b)lesbians of the “butch” type behaving like men; (c) lesbians of the “femme”type likewomen; and (d) lesbian of the “andro”type whocan be like men and women. Second,the interactions include: (a) the interaction of lesbian characters with fellow lesbians inan overt manner, and (b) the interaction of lesbian characters with family and society ina covert manner. Third, lesbian characters struggle to maintain their existence. Fourth,the views of other figures on the existence of lesbian characters are partly positive andpartly negative.Keywords: lesbian images, feminism, Indonesian novels, female writers